Philosophies and Sociologies of Bioethics Crossing the divides (Springer International Publishing, 2018)
This book is an interdisciplinary contribution to bioethics, bringing together philosophers, sociologists and Science and Technology Studies researchers as a way of bridging the disciplinary divides that have opened up in the study of bioethics. Each discipline approaches the topic through its own lens providing either normative statements or empirical studies, and the distance between the disciplines is heightened not only by differences in approach, but also disagreements over the values, interpretations and problematics within bioethical research. In order to converse across these divides, this volume includes contributions from several disciplines. The volume examines the sociological issues faced by interdisciplinary research in bioethics, the role of expertise, moral generalisations, distributed agency, and the importance of examining what is not being talked about. Other contributions try to take an interdisciplinary look at a range of specific situations, fetal alcohol syndrome in the media, citizen science, electronic cigarettes and bioethical issues in human geography.